PROJETO SEMEANDO SAÚDE – 1ST EDITION: INTEGRATION BETWEEN THE COMMUNITY AND FUTURE PHYSICIANS (CIPEEX, 2025)
The current academic sphere has highlighted the influence of activities that go beyond the technical knowledge applied in educational centers, such as the transmission of learning to the surrounding community, with the aim of fostering reflection and changes in behavior. Thus, this work aims to report the experience of implementing the extension project PROJETO SEMEANDO SAÚDE – 1st Edition, whose objective was to apply the knowledge acquired during the first semester of class XXVII of the Medical School at the Universidade Evangélica de Goiás. A total of 18 educational workshops were developed for children and adults, and as an evaluation method, the medical students answered a questionnaire regarding the impact of the activities carried out. The results obtained from the analysis of the responses demonstrate the participants’ recognition of the importance of the project for the development of their medical knowledge as well as communicative and leadership skills. Therefore, it is evident that the workshops conducted in the community are essential for the consolidation of academic knowledge, in addition to fostering human, supportive, and empathetic characteristics.
Keywords: Community extension; Health promotion; Medical students